الشروط الجزائية في عقد الإجارة المنتهية بالتمليك = The penalty clauses in leasing contract which ends with ownership (al-Ijārah al-Muntahiyah bi al-Tamlīk) - Salim al-Sinani, Said; Zakaria, Mohamad Sabri; Md. Sawari, Mohd. Fuad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The study of penal clauses is one of the most important aspects that should be jurisprudentially studied and highlighted. This is because in their contracts, most of the Islamic banks have stipulated several penal conditions to preserve their financial rights, achieve guarantees, reduce their risks in dealing with customers, address the problem of procrastination in debt settlement and financial obligations. No contract exists without a set of penal clauses, such as the condition of penalty for delay in the event of late payment, the requirement that the expenses of the lawsuit should be paid by the procrastinator of debt and other conditions. There is an urgent need to study these penal conditions and identify the extent to which they agree or disagree with the rulings of Islamic Shariah so that the transactions of Islamic banks can be free of forbidden or suspicious transactions, especially those in which there is ribā or suspicion of ribā. This paper is an attempt to highlight the position of Sharia on the penal conditions applied in the Ijārah contract that leads to ownership.